(Nie)obecność Juliana Tuwima na Litwie - Dalecka, Teresa (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
The reception of Polish literature in Lithuania is a complex phenomenon. For a long time there was a dominant trend of expanding the area of Lithuanian literature by incorporating into it some of the Polish-language authors who maintained contacts with Lithuania. As a result, the horizons of national literature naturally broadened. However, the reception of Julian Tuwim’s writing belongs to a different category. It needs to be remembered that in the Soviet period Polish literature offered Lithuanian intellectuals a passage to the outside world. It was in the work of western poets, Tuwim’s work included, that Lithuanian authors sought ways of expanding their avant-garde forms and dictions. Tuwim’s poetry has been largely read in its original, Polish version; therefore, there are few books collecting his poems. However, the influence of Tuwim’s work is recognized by some experts in translations of his work. However, Tuwim was made publicly known in Lithuania thanks an argument over the naming one of the street in Vilnius after his name. The article analysis public reactions to this argument and shows how this non-literary event made Tuwim a public figure in the country.